2016
DOI: 10.1038/nature18319
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt plate accelerations shape rifted continental margins

Abstract: Rifted margins are formed by persistent stretching of continental lithosphere until breakup is achieved. It is well known that strain-rate-dependent processes control rift evolution, yet quantified extension histories of Earth's major passive margins have become available only recently. Here we investigate rift kinematics globally by applying a new geotectonic analysis technique to revised global plate reconstructions. We find that rifted margins feature an initial, slow rift phase (less than ten millimetres p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
160
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 67 publications
17
160
0
1
Order By: Relevance
“…Figure 1(c) shows a sectional schematic representation of the coupled numerical model with depth-dependent layered mantle viscosity structure ( Figure 1b) and seismic velocity-to-density scaling profile of Steinberger and Calderwood (2006) (Figure 1a), which are only considered below the depth of 300 km. The top 10 thermo-mechanical component (SLIM3D) has been used in a wide range of 2D and 3D regional numerical studies of crustal and lithospheric deformations (Popov and Sobolev, 2008;Brune et al, 2012Brune et al, , 2014Brune et al, , 2016Popov et al, 2012;Quinteros and Sobolev, 2013) with different spatial and temporal resolutions but the coupled code is used here and in Osei for the first time. In this 3D global study, we distinguish three material layers (phases) within the top component (SLIM3D): the crustal layer, the lithosphere and the sub-lithospheric mantle layers in order to account for the stress and temperature- visco-elasto-plastic rheology is described in detail by (Popov and Sobolev, 2008), with specific modeling parameters given in Osei and here in the appendix.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Figure 1(c) shows a sectional schematic representation of the coupled numerical model with depth-dependent layered mantle viscosity structure ( Figure 1b) and seismic velocity-to-density scaling profile of Steinberger and Calderwood (2006) (Figure 1a), which are only considered below the depth of 300 km. The top 10 thermo-mechanical component (SLIM3D) has been used in a wide range of 2D and 3D regional numerical studies of crustal and lithospheric deformations (Popov and Sobolev, 2008;Brune et al, 2012Brune et al, , 2014Brune et al, , 2016Popov et al, 2012;Quinteros and Sobolev, 2013) with different spatial and temporal resolutions but the coupled code is used here and in Osei for the first time. In this 3D global study, we distinguish three material layers (phases) within the top component (SLIM3D): the crustal layer, the lithosphere and the sub-lithospheric mantle layers in order to account for the stress and temperature- visco-elasto-plastic rheology is described in detail by (Popov and Sobolev, 2008), with specific modeling parameters given in Osei and here in the appendix.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Cande & Stegman 2011). A recent study proposes abrupt plate accelerations before continental rupture due to a rapid decrease in rift strength (Brune et al 2016).…”
Section: Subduction In the Pacific And Mediterranean Realms And The mentioning
confidence: 99%
“…The dynamics of the lithosphere is determined by a combination of plastic, elastic and viscous flow properties of the lithospheric material (Burov, 2011;Tesauro et al, 2012), while the evolution of the sub-lithospheric mantle is predominantly driven by viscous flow (Davies, 1977;Forte and Mitrovica, 2001;Steinberger and Calderwood, 2006). It has been shown that shallow processes influence both the magnitude and orientation of the lithospheric stresses.…”
Section: Introductionmentioning
confidence: 99%